Detection of senescence-associated heterochromatin foci (SAHF) - Aird, Katherine M. (2013)
Senescence-associated heterochromatin foci (SAHF) are specialized domains of facultative heterochromatin that contribute to silencing of proliferation-promoting genes (such as E2F target genes) in senescent cells. Thus, methods for detection of SAHF are invaluable tools in the field of senescence to identify these distinct changes in heterochromatin that are associated with the senescence-associated cell cycle exit. Here, we describe fluorescent-based methods for the detection of SAHF in senescent cells, including examining reorganization of DNA structure by 4′,6-diamidino-2-phenylindole (DAPI) staining and using specific antibodies to components of SAHF such as the histone H2A variant macroH2A, heterochromatin protein 1 (HP1) proteins and lysine 9 di-or tri-methylated histone H3 (H3K9Me2/3). Together, these markers identify SAHF, the distinct facultative heterochromatin structures that are associated with senescent cells.